MANAJEMEN KONFLIK DALAM LEMBAGA PENDIDIKAN ISLAM : PENDEKATAN ISLAMI DAN KONTEMPORER - Febi Febrianda; Junaidi Junaidi (CV. ADIBA ASIHA AMIRA, 2025)
This research is motivated by the many conflicts that occur in the current Islamic educational institution environment, both in terms of learning and educational administration. The purpose of this study is to find out conflict management in Islamic educational institutions using Islamic and contemporary approaches. The method of this research is to use a literature study study. The result of this study is that the occurrence of conflicts in Islamic educational institutions is something that is common, considering that Islamic educational institutions are still continuing to carry out the process of improvement in their systems and mechanisms. Conflicts also arise because they are caused by the unpreparedness of facilities and infrastructure that support their implementation and the existence of differences and contradictions in the implementation of the implementation mechanism of Islamic educational institutions, even conflicts also arise because of conflicts in the behavior of practitioners of Islamic educational institutions themselves. In an Islamic perspective, conflicts must be managed properly so that they become a force for the better and can facilitate the implementation of a stable and consistent education system. One of the postulates in conflict management in Islam is contained in Q.S Annisa verse 35, which explains that conflicts must be overcome and solutions must be found. Meanwhile, in the current contemporary approach, conflict management can be done by utilizing science and technology as a tool to minimize and normalize everything that is deemed necessary to reduce and resolve conflicts that occur. If conflicts are left unattended and not managed with appropriate conflict management, it will have a bad impact, especially on the success of Islamic educational institutions. The Islamic and Contemporary approaches are two viewpoints that can help resolve conflicts that occur in the environment of Islamic educational institutions. In other words, Islam is a religion that is always present to provide solutions to all problems, including conflict management. However, on the other hand, it is also necessary to look at the current situation and conditions by looking at the development of the increasingly advanced times, of course it is necessary to solve problems by considering the conditions in the current contemporary era.